Design Research in Information Systems - Hevner, Alan; Chatterjee, Samir (Springer, 2010)
The creative human activity of design changes the world in which we live for the better. As academic researchers in the field of information systems (IS), the co-authors have observed, studied, and taught design in the development of software-intensive systems for business. We have experienced the difficulties and wicked nature of designing useful systems. More importantly, we have faced classrooms of students with the challenges of how teach the underlying theories and everyday practices of software system design. These experiences and challenges have motivated us to perform research in the science of design, or design science research (DSR), and to write this book. We believe that the study of information systems design, both its theory and practice, has become an essential part of the education of IS students and professionals. More and more IS graduate and doctoral programs are beginning to offer graduatelevel seminars on design science research. The purpose of this book is to fill a void: the lack of a good reference book on design science research. Most current seminars study a collection of research papers from many sources. Often, these papers are written with differing terminology and research perspectives leading to confusion and misunderstandings for students. Here we provide a consistent approach for performing and understanding design science research while maintaining a diversity of opinions from many thought leaders in the IS design community.
Theory and Practice